Features of Mpox infection: The analysis of the data submitted to the ID-IRI network - Eser-Karlidag, Gulden; Chacon-Cruz, Enrique; Cag, Yasemin; Martinez-Orozco, Jose Arturo; Gudino-Solorio, Humberto; Cruz-Flores, Raul Adrian; Gonzalez-Rodriguez, Andrea; Martinez-Nieves, Daniela; Gomez-Zepeda, Mario; Calderon-Suarez, Andrea; Çaşkurlu, Hülya; Cascio, Antonio; et al. (Elsevier, 2023)
Background: Mpox is a rare zoonotic disease caused by the Mpox virus. On May 21, 2022, WHO announced the emergence of confirmed Mpox cases in countries outside the endemic areas in Central and West Africa. Methods: This multicentre study was performed through the Infectious Diseases International Research Initiative network. Nineteen collaborating centres in 16 countries participated in the study. Consecutive cases with positive Mpoxv-DNA results by the polymerase chain reaction test were included in the study. Results: The mean age of 647 patients included in the study was 34.5.98.6% of cases were males, 95.3% were homosexual-bisexual, and 92.2% had a history of sexual contact. History of smallpox vaccination was present in 3.4% of cases. The median incubation period was 7.0 days. The most common symptoms and signs were rashes in 99.5%, lymphadenopathy in 65.1%, and fever in 54.9%. HIV infection was present in 93.8% of cases, and 17.8% were followed up in the hospital for further treatment. In the two weeks before the rash, prodromal symptoms occurred in 52.8% of cases. The incubation period was 3.5 days shorter in HIV-infected Mpox cases with CD4 count <200/μL, we disclosed the presence of lymphadenopathy, a characteristic finding for Mpox, accompanied the disease to a lesser extent in cases with smallpox vaccination. Conclusions: Mpox disseminates globally, not just in the endemic areas. Knowledge of clinical features, disease transmission kinetics, and rapid and effective implementation of public health measures are paramount, as reflected by our findings in this study.
Keywords: HIV-Infected mpox; Mpox; Outbreak; Smallpox vaccine